2010
DOI: 10.1088/0022-3727/43/28/285001
|View full text |Cite
|
Sign up to set email alerts
|

Thin films of the Heusler alloys Cu2MnAl and Co2MnSi: recovery of ferromagnetism via solid-state crystallization from the x-ray amorphous state

Abstract: X-ray amorphous thin films of the Heusler alloys Cu 2 MnAl and Co 2 MnSi have been prepared by magnetron sputter deposition at room temperature. In the amorphous state the Cu 2 MnAl phase is non-ferromagnetic; Co 2 MnSi is weakly ferromagnetic with a ferromagnetic Curie temperature of 170 K. By solid-state crystallization at high temperatures strong ferromagnetic order and high Curie temperatures are established in both alloys. The saturation magnetization of the Co 2 MnSi alloy reaches 5.1µ B /f.u. at 4 K, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 49 publications
4
13
0
Order By: Relevance
“…For amorphous S RT and S 300 , long-range crystallographic structure breaks, resulting in the small M S compared with the polycrystalline samples. Similar phenomena have also been reported by other group [34]. Interestingly, we found that there exists a dual behavior in magnetic moment at low magnetic fields for the polycrystalline samples.…”
Section: Samplesupporting
confidence: 92%
See 1 more Smart Citation
“…For amorphous S RT and S 300 , long-range crystallographic structure breaks, resulting in the small M S compared with the polycrystalline samples. Similar phenomena have also been reported by other group [34]. Interestingly, we found that there exists a dual behavior in magnetic moment at low magnetic fields for the polycrystalline samples.…”
Section: Samplesupporting
confidence: 92%
“…According to the calculation of Kubler et al [33] on X 2 MnY Heusler alloys, the ferromagnetism of perfectly ordered CMS films (namely in L2 1 phase) comes from ferromagnetic Co-Co and Co-Mn sites interaction, and no nearest Mn-Mn sites exist in the L2 1 films. Therefore, the next-nearest Mn-Y-Mn indirect exchange dominates the ferromagnetic properties [34][35][36][37][38]. While in less ordered states (D0 3 , B2 or A2 phase), the appearance of anti-site disorder leads to the probable nearest Mn-Mn sites, which further results in the strong antiferromagnetic interaction, competing with the Co-Co and Co-Mn ferromagnetic interactions.…”
Section: Samplementioning
confidence: 99%
“…For the Co2MnGe layers prepared at RT, we observe lower (220) BP intensities and an almost vanishing (440) peak. The BPs associated with (110) order (L21 and/or B2) do not imply that the entire sample is ordered, they signify only a fractional presence of such ordering in the samples . In that sense lower intensities of BPs for the RT grown Heusler layers indicate larger disorder of Co2MnGe in comparison with the one prepared at 400C.…”
Section: Experiments and Resultsmentioning
confidence: 94%
“…5 This alloy was found to exhibit a ferromagnetic behavior with a saturation magnetization of 5.1 l B /f.u. at 4 K. 6 However, the highest Curie temperature of 1100 K has been reported for Co 2 FeSi Heusler alloy, with a ferromagnetic half-metallic behavior and a total magnetic moment of 6.0l B /f.u. measured at 5 K. 7,8 Moreover, a theoretical study by Lee et al has predicted a half metallic behavior for Co 2 TiZ (Z ¼ Al, Si, Ga, Ge, and Sn) Heusler alloys.…”
mentioning
confidence: 99%